2019
DOI: 10.1038/s41598-019-40478-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional stability analyses of maxillofacial skeleton bearing cleft deformities

Abstract: The symmetrically stable craniofacial bony structure supports the complex functions and delicate contour of the face. Congenital craniofacial deformities are often accompanied by bony defects and have been repetitively correlated with compromised dento-maxillary stability, but neither the extent nor the pattern of cleft-related maxillary instability has been explored in detail. Furthermore, it is largely unknown if the bony defect and related instability are correlated with secondary maxillary deformity common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Approximately 75% of patients with cleft lip and palate have varying degrees of alveolar cleft [ 20 ]. UCLP (Unilateral Cleft Lip and Palate) deformity has a significant impact on the bone morphology of the mid-facial and oronasal regions [ 21 ], the alveolar process on the non-cleft side is more prominent and protuberant than that on the cleft side [ 2 ]. There are asymmetrical bone movements in UCLP due to the special maxillofacial structure [ 22 ], loss of bone and soft tissue on the cleft side and tension of the repaired lip on the non-cleft side can lead to flattening and recession of the central face [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 75% of patients with cleft lip and palate have varying degrees of alveolar cleft [ 20 ]. UCLP (Unilateral Cleft Lip and Palate) deformity has a significant impact on the bone morphology of the mid-facial and oronasal regions [ 21 ], the alveolar process on the non-cleft side is more prominent and protuberant than that on the cleft side [ 2 ]. There are asymmetrical bone movements in UCLP due to the special maxillofacial structure [ 22 ], loss of bone and soft tissue on the cleft side and tension of the repaired lip on the non-cleft side can lead to flattening and recession of the central face [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on epidemiological statistics, Nagase et al [ 1 ] found UCCLP (unilateral complete cleft lip and palate) to be the most prevalent type of cleft lip and palate. For patients with UCCLP, the two parts of the maxilla divided by the cleft are also different [ 2 ],the asymmetry of the nasomaxillary complexes [ 3 , 4 ] and the congenital sagittal asymmetric defect of the maxilla with collapsed bone segment deformity [ 5 ] on the cleft side are the common clinical manifestations. According to the summary by Janovica et al [ 6 ], the occlusal forces of the dentition formed the specific bony conduction trajectories along the thickened buttresses of the maxillofacial bones, comprising a total of 7 vertical buttresses (bilateral nasomaxillary, zygomaticomaxillary, pterygomaxillary buttresses and the median sagittal buttress) and 3 horizontal buttresses (bilateral prefrontal, zygomatic and maxillary buttresses) to transmit the majority of occlusal loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason why the growth of the middle facial third in patients with CLP may be altered is the bone asymmetry of the upper maxilla caused by a cleft. Asymmetric deformation is produced during mastication and deviation of occlusal forces in the cranio-maxillo-facial complex as well as different types of mastication between unilateral and bilateral patients with CLP, causing asymmetric stimuli in growth areas and inducing changes in the development of the maxillofacial complex (Luo et al, 2019). This finding is related to the differences in craniofacial growth and development observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cleft lip and/or palate (CL/P) is the most common birth defect around the world (Xiangyou et al, 2019). The occurrence is recorded to generally impact one in every 700 live births worldwide but cleft cases in South-East Asian countries seem to be higher where the prevalence is between 1.1 and 1.9 per 1000 live births (Abumustafa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%